2019
DOI: 10.1186/s40635-019-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effects of crystalloid and colloid volume resuscitation on primary, derived and efficiency variables in post-CABG patients

Abstract: Background Recent studies in haemodynamic management have focused on fluid management and assessed its effects in terms of increase in cardiac output based on fluid challenges or variations in pulse pressure caused by cyclical positive pressure ventilation. The theoretical scope may be characterised as Starling-oriented. This approach ignores the actual events of right-sided excitation and left-sided response which is consistently described in a Guyton-oriented model of the cardiovascular system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
3
0
0
Order By: Relevance
“…The calculated initial stressed volume was quite similar to the 1.7 l reported in a previous study of P ms 20 and corresponds well to a proportion of 30% of the total blood volume demonstrated during no‐flow conditions on cardiopulmonary bypass 21 . The baseline P msa in this study is very similar to the 15‐18 mm Hg found previously in three smaller studies of postoperative cardiac surgery patients using the same mathematical model 11,12,22 . The range of P msa is furthermore similar to the mean systemic filling pressure of 18‐21 mm Hg obtained from successive inspiratory hold manoeuvres in patients following cardiac surgery 20,23 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The calculated initial stressed volume was quite similar to the 1.7 l reported in a previous study of P ms 20 and corresponds well to a proportion of 30% of the total blood volume demonstrated during no‐flow conditions on cardiopulmonary bypass 21 . The baseline P msa in this study is very similar to the 15‐18 mm Hg found previously in three smaller studies of postoperative cardiac surgery patients using the same mathematical model 11,12,22 . The range of P msa is furthermore similar to the mean systemic filling pressure of 18‐21 mm Hg obtained from successive inspiratory hold manoeuvres in patients following cardiac surgery 20,23 .…”
Section: Discussionsupporting
confidence: 88%
“…The range of P msa is furthermore similar to the mean systemic filling pressure of 18‐21 mm Hg obtained from successive inspiratory hold manoeuvres in patients following cardiac surgery 20,23 . The increased P msa following boluses is consistent with responses to volume loading reported earlier following cardiac surgery, 11‐13,20,22,23 hepatic surgery 24 as well as in general ICU patients 25 . Taken together, these studies lend credibility to the concept of using P msa to assess volume state and responses to increased intravascular filling.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, 100 ml of colloids did significantly increase MSFP, whereas 100 ml of crystalloids did not. A previous study also found the response on crystalloid variable in post-CABG patients (Sondergaard et al, 2019). Perhaps a capillary leak syndrome with endothelial glycocalyx shedding can partly explain our results, or that the expected transudation of crystalloid into the interstitium occurred rapidly in patients after cardiac surgery (Dekker et al, 2019).…”
Section: Clinical Feasibilitysupporting
confidence: 70%